The Importance of Commissioners Board Diversity in CSR Disclosures - Anita Ade Rahma; Febri Aldi (Yayasan Riset dan Pengembangan Intelektual, 2020)
Good companies are inseparable from good Corporate Social Responsibility (CSR). CSR is one indication of whether or not a company is good or bad. CSR has a real impact on the environment and society. The better the impact obtained from the company's CSR, the better the company's performance. CSR activities can be seen from the CSR disclosures. CSR disclosure is influenced by various internal and external factors. As for this study, we want to analyze the influence of the diversity of the board of commissioners on CSR disclosure. The independent variables used in this study are gender commissioners, nationality commissioners, and ethnic commissioners. Company data used are from LQ45 companies listed on the Indonesia Stock Exchange in 2015-2017. 20 companies were found to be the sample of this study using purposive sampling method. From the data processing that has been done, the results obtained are that Gender commissioners have no effect on CSR disclosure. Likewise, the Nationality commissioner proved not to affect the increase in CSR disclosure. but conversely with Ethnic commissioners who have a significant influence on CSR disclosure. This means that ethnic diversity on the board of commissioners is very important. In addition to expanding CSR disclosure can also improve company performance.